Effect of a starter concentrate and a litter fence on the productive performance of lactating guinea pigs - Soto Mateo, Carmen (2020)
The aim of this study was the use of starter concentrate and litter fences in lactating guinea pigs until weaning (15 days). The treatments were: TI, Conventional concentrate (CC) and without litter fence; Control; TII, CC + litter fence; TIII, CC + start concentrate + litter fence. Body weight gain, feed intake and mortality at weaning were evaluated. Nine 1 m2 pits with 5 females and 1 male per pit and litter fences (triangular shape with an area of 0.125 m2) were used (TII and TIII) where clay feeders for the starting concentrate were located (20% protein and 2781 kcal/kg of digestible energy). The conventional (commercial) concentrate for mothers provided 18.7% protein and 2888 kcal/kg of digestible energy. The body weight gain at weaning was 10.3, 9.5 and 9.3 g/d for T I, II and III, respectively, with no significant difference between them. The consumption of concentrate of the offspring was similar between TII (19.4 g/d) and TIII (18.4 g/d) and the percentage of mortality at weaning was 11,5, 13.9 and 8.0% for T I, II and III, respectively.